2020
DOI: 10.1111/1365-2745.13563
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity predominantly determines long‐term biocrust‐forming lichen cover in drylands under climate change

Abstract: 1. Manipulative experiments typically show a decrease in dryland biocrust cover and altered species composition under climate change. Biocrust-forming lichens, such as the globally distributed Diploschistes diacapsis, are particularly affected and show a decrease in cover with simulated climate change. However, the underlying mechanisms are not fully understood, and long-term interacting effects of different drivers are largely unknown due to the short-term nature of the experimental studies conducted so far. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 98 publications
2
22
0
Order By: Relevance
“…These observed correlations apply to the full range and the two parts of our elevation gradient and also align with previous experimental findings (e.g. Baldauf et al, 2021), suggesting that these different responses could be partially explained by contrasting physiological tolerance. However, as with vascular plants, the effect of climate variables on bryophytes–lichens and soil phototrophs was also mediated by other factors, with fire playing a central role (see Palmer et al, 2020 for review).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observed correlations apply to the full range and the two parts of our elevation gradient and also align with previous experimental findings (e.g. Baldauf et al, 2021), suggesting that these different responses could be partially explained by contrasting physiological tolerance. However, as with vascular plants, the effect of climate variables on bryophytes–lichens and soil phototrophs was also mediated by other factors, with fire playing a central role (see Palmer et al, 2020 for review).…”
Section: Discussionsupporting
confidence: 92%
“…Grau et al, 2007). Like vascular plants, non‐vascular terrestrial cryptogams and soil phototrophs, key components of biological soil crusts, are climate sensitive (Baldauf et al, 2021; Di Nuzzo et al, 2021; Rodríguez‐Caballero et al, 2018). Yet, they are also susceptible to disturbance such as fire (Palmer et al, 2020), and the impact of climate variables on their diversity patterns could be indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulative experiments and process models concur that a warmer, drier future will generally reduce abundance and the rate of carbon fixation in biocrusts (Baldauf et al, 2021;de Guevara et al, 2014;Reed et al, 2016;Zhang et al, 2018). Our stoichiometry results…”
Section: Discussionsupporting
confidence: 66%
“…Because water availability is so closely tied to carbon fixation in poikilohydric organisms (Raggio et al., 2021), the increasing scarcity of water means that biocrust carbon stocks are likely to decline at the global scale. Manipulative experiments and process models concur that a warmer, drier future will generally reduce abundance and the rate of carbon fixation in biocrusts (Baldauf et al., 2021; de Guevara et al., 2014; Reed et al., 2016; Zhang et al., 2018). Our stoichiometry results along an aridity gradient reinforce the carbon fixation results of prior work and agree with a recent mesocosm study, which found that simulated warming and rainfall reduction led to reduced tissue C:N in a biocrust lichen (Concostrina‐Zubiri et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As already noted by previous research (Amthor et al, 2010 ; Beier et al, 2004 ; Bruhn et al, 2013 ), this effect represents an artifact introduced by experimental temperature manipulation. Dewfall represents an important source of water for ecosystems in arid and semiarid areas (Uclés et al, 2014 ), especially for biocrust formation (Baldauf et al, 2021 ). In our experiment, however, the predawn leaf water potential of C. monspeliensis was not modified by warming, even during dry periods, indicating that both nighttime soil warming and reduced dew formation did not significantly modify plant water balance.…”
Section: Discussionmentioning
confidence: 99%